2017
DOI: 10.1111/jar.12385
|View full text |Cite
|
Sign up to set email alerts
|

Relation between working memory and self‐regulation capacities and the level of social skills acquisition in people with moderate intellectual disability

Abstract: As WM had a greater influence on social skills, incorporating WM training into programmes for improving social skills in persons with MID should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 70 publications
0
6
0
2
Order By: Relevance
“…Working memory has three components according to the cognitive model proposed by Baddeley []: a central executive, an episodic buffer, and two slave systems (the phonological loop and the visuospatial sketchpad as the visuospatial working memory, VSWM) [Barendse et al, ]. VSWM supports memory for objects, faces, and scenes [Dučić, Gligorović, & Kaljača, ; Vandenbroucke et al, ; Wilde, Koot, & Lier, ]. VSWM deficits are often found in ASD and ADHD [Klingberg et al, ; Van et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Working memory has three components according to the cognitive model proposed by Baddeley []: a central executive, an episodic buffer, and two slave systems (the phonological loop and the visuospatial sketchpad as the visuospatial working memory, VSWM) [Barendse et al, ]. VSWM supports memory for objects, faces, and scenes [Dučić, Gligorović, & Kaljača, ; Vandenbroucke et al, ; Wilde, Koot, & Lier, ]. VSWM deficits are often found in ASD and ADHD [Klingberg et al, ; Van et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Quanto à análise de dados dos estudos, nota-se uma ampla utilização do Pacote Estatístico para Ciências Sociais (SPSS), em variadas versões, de métodos estatísticos, principalmente, as medidas de tendência central e variabilidade e o uso da ANOVA para análise de variância da população amostral. Sobre os resultados dos estudos, todos os que se propuseram a realizar intervenções indicaram resultados positivos em relação à aquisição, manutenção e generalização de comportamentos de habilidades sociais (Adeniyi & Omigbodun, 2016;Ashburner, Bobir, & van Dooren, 2018;Dučić, Gligorović, & Kaljača, 2018;Ferreira & Munster, 2017;Garrels, 2019;Gilson & Carter, 2016;Guivarch et al, 2017;Khodabakhshi-Kooalee, Falsafinejad, & Rezaei, 2018;Lappa & Mantzikos, 2019;Plavnick, Kaid, & MacFarland, 2015;O'Handley, Ford, Radley, Helbig, & Wimberly, 2016;Oxelgren et al, 2019;Özokcu, Akçamete, & Özyürek, 2017;Ryan, Brady, Holloway, & Lydon, 2019;Stauch, Plavnick, Sankar, & Gallagher, 2018).…”
Section: Resultsunclassified
“…With regard to the training design, the content could cover a variety of skills learning such as goal-setting and planning skills, problem-solving skills, decision-making skills and self-regulatory skills. Hence, it is suggested that the elements of working memory, a main component of executive function, and emotion regulation be included in the instructional strategies as previous studies provided evidence that these two elements facilitate skills acquisition by people with ID [46,47]. Employing slogans as well as visual cues such as flow charts and videos during training would help people with ID acquire a better working memory as it would facilitate them to learn self-determined skills and apply those skills in their daily lives.…”
Section: Discussionmentioning
confidence: 99%